2013
DOI: 10.1371/journal.pone.0056457
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Jasmonic Acid Plant Defence Pathway Alters the Composition of Rhizosphere Bacterial Communities

Abstract: Jasmonic acid (JA) signalling plays a central role in plant defences against necrotrophic pathogens and herbivorous insects, which afflict both roots and shoots. This pathway is also activated following the interaction with beneficial microbes that may lead to induced systemic resistance. Activation of the JA signalling pathway via application of methyl jasmonate (MeJA) alters the composition of carbon containing compounds released by roots, which are implicated as key determinants of rhizosphere microbial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 44 publications
(51 reference statements)
5
94
2
5
Order By: Relevance
“…For example, a study involving SIP assessed how plant-fixed carbon is translocated belowground under elevated atmospheric carbon dioxide [191] and 16S rRNA amplicon sequencing of plants treated with defense hormones has revealed that plants are able to alter their rhizosphere bacterial community to recruit potentially beneficial microbes that assist in plant defense [160].…”
Section: Choice Of Methods and Complimentary Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study involving SIP assessed how plant-fixed carbon is translocated belowground under elevated atmospheric carbon dioxide [191] and 16S rRNA amplicon sequencing of plants treated with defense hormones has revealed that plants are able to alter their rhizosphere bacterial community to recruit potentially beneficial microbes that assist in plant defense [160].…”
Section: Choice Of Methods and Complimentary Approachesmentioning
confidence: 99%
“…Due to reasonably longer sequences compared to the other high-throughput sequencing platforms (see below sections) and higher output compared to conventional cloning sequencing approaches, pyrosequencing allows the detection of rare bacterial and archaea genera. Recently, this method has been extensively used to characterize composition and diversity of soil microbial communities [20,107,[160][161][162][163] and has also been applied to understand the effect of heavy metals and disturbances on soil microbial communities [162,164,165]. The particularity of this method is that it provides reads that are long enough (average 500 bp but up to 1000 bp) to assign probable taxonomic identity up to genus level and rare groups can be detected as thousands of reads can be obtained per sample.…”
Section: High-throughput Sequencing Technologiesmentioning
confidence: 99%
“…Rhizosphere is a complex ecosystem characterized by a large amount of microniches-spatially close, but chemically heterogeneous-containing a high diversity of microorganisms [74]. The structure of the rhizosphere microbial community depends on soil type [75][76][77][78], temporal changes (seasons) and environmental factors [79,80], plant species and genotype [75,[81][82][83][84][85], plant development stage [85][86][87] and signaling of plant hormones [88]. [16,17,66].…”
Section: Actors Of Phytoremediation: the Holobiontmentioning
confidence: 99%
“…Mit den neuen Methoden der Genom-und Phänotypi-sierungsanalyse werden die dabei involvierten Stoffwechsel-und Signaltransduktionswege der Pflanzen sowie der Mikroorganismen erforscht (Zamioudis et al, 2013). Dabei werden "next-generation sequencing", DNA Microarrays und Proteomik genutzt (Berlec, 2012 (Carvalhais et al, 2013). Andererseits werden bestimmte Signaltransduktionswege in der Pflanze erst durch die Interaktion mit bestimmten nützlichen Mikroben aktiviert.…”
Section: Pflanzenwachstum Fördernde Nutzbakterienunclassified